Evaluation of clinical and laboratory characteristics of patients with cutaneous sarcoidosis: A single-center retrospective cohort study - Boch, Katharina; Langan, Ewan A.; Zillikens, Detlef; Ludwig, Ralf J.; Kridin, Khalaf (Frontiers in Medicine, 2022)
Background Cutaneous sarcoidosis is a relatively rare disease whose clinical manifestations include red-brown macules, plaques, papules and subcutaneous nodules. The skin changes may also be restricted to pre-existing scars. Cutaneous sarcoidosis can be associated with systemic organ involvement. Objectives Aim of this retrospective study was to longitudinally investigate clinical and laboratory findings in patients with cutaneous sarcoidosis. Methods Patients (>18 years) with histologically confirmed cutaneous sarcoidosis between January 2014 and December 2020 were included. Patient demographics, clinical features, laboratory and radiological findings, management, clinical outcomes and co-morbidities associated with cutaneous sarcoidosis were analyzed. Results Thirty-seven patients with cutaneous sarcoidosis were identified, of whom 57% were female. The most common clinical phenotype of cutaneous sarcoidosis was papular sarcoidosis (n = 16), while plaques and nodules were present in 9 patients. In contrast, subcutaneous (n = 1) and scar-associated sarcoidosis (n = 1) were rare. Of patients with systemic disease, the cutaneous disease followed, preceded, and coincided with the development of systemic sarcoidosis in 2, 9, and 12 patients, respectively. Levels of soluble interleukin (IL)-2 receptor, angiotensin converting enzyme (ACE), and C-reactive protein (CRP) were elevated, in 76%, 21%, and 50% of the tested patients respectively and predicted systemic involvement. Hypercalcemia was present in 6% of patients. Female sex and younger age (<54 years) were significantly associated with systemic manifestations. Conlcusions Cutaneous sarcoidosis was frequently associated with additional systemic involvement, particularly when present in young females. 24 % of patients with cutaneous sarcoidosis developed additional organ involvement during follow-up.